Linking psychological capital, technology readiness and entrepreneurial orientation to entrepreneurs' financial performance: a study of women MSMEs in Indonesia - Anissa Lestari Kadiyono; Rezki Ashriyana Sulistiobudi (Cogent Business & Management, 2024)
This study investigates the entrepreneurial financial performance of women micro, small, and medium enterprise (MSME) actors in Indonesia, drawing upon social cognitive theory to assess the interplay of psychological capital (PsyCap), technology readiness, and entrepreneurial orientation. Recognizing women entrepreneurs in MSMEs as pivotal economic contributors, this study examined the moderating effect of technology readiness on the entrepreneurial outcomes facilitated by PsyCap. Simultaneously, we explore how entrepreneurial orientation mediates this relationship. The sample comprised 920 female MSME actors from West Java, D.I.Y. Yogyakarta, and West Sumatra, selected through quota sampling. Data were collected via self-reported questionnaires measuring PsyCap, technology readiness, entrepreneurial orientation, and entrepreneurs' financial performance. The data was analyzed using structural equation modeling. These findings indicate that technological readiness significantly moderates the relationship between PsyCap and entrepreneurs' financial performance. Although technology readiness directly influences entrepreneurial orientation, it does not alter the overall model's efficacy. This suggests that technology readiness can enhance performance, but it does not impact the PsyCap factors that propel women entrepreneurs' financial performance. These insights can inform potential government interventions to bolster female entrepreneurship. This study contributes novel empirical evidence to entrepreneurial literature by presenting a comprehensive model that elucidates the mediating and moderating processes necessary for fostering entrepreneurial financial performance. It offers practical implications for SME governance and policymakers aiming to elevate the competitive stance of women entrepreneurs in a demanding business ecosystem.
Keywords: 650; social cognitive theory perspective; women's entrepreneur financial performance; psychological capital; technology readiness; entrepreneur orientation